Association between participation in the Families First Home Visiting programme and First Nations families' public health outcomes in Manitoba, Canada: a retrospective cohort study using linked administrative data. Issue 6 (28th June 2019) - Enns, Jennifer E; Chartier, Mariette; Nickel, Nathan; Chateau, Dan; Campbell, Rhonda; Phillips-Beck, Wanda; Sarkar, Joykrishna; Burland, Elaine; Lee, Janelle Boram; Katz, Alan; Santos, Rob; Brownell, Marni
Abstract : Objective: To determine whether the Families First Home Visiting (FFHV) programme, which provides home visiting services to families across Manitoba, is associated with improved public health outcomes among First Nations families facing multiple parenting challenges. Design: Retrospective cohort study using population-based administrative data. Setting: Manitoba, Canada. Participants: First Nations children born in Manitoba in 2003–2009 (n=4010) and their parents enrolled in FFHV compared with non-enrolled families with a similar risk profile. Intervention: FFHV supports public health in Manitoba by providing home visiting services to First Nations and non-First Nations families with preschool children and connecting them with resources in their communities. Outcomes: Predicted probability (PP) and relative risk (RR) of childhood vaccination, parental involvement in community support programmes and children's development at school entry. Results: FFHV participation was associated with higher rates of complete childhood vaccination at age 1 (PP: FFHV 0.715, no FFHV 0.661, RR 1.08, 95% CI 1.03 to 1.14) and age 2 (PP: FFHV 0.465, no FFHV 0.401, RR 1.16, 95% CI 1.08 to 1.25), and with parental involvement in community support groups (PP: FFHV 0.149, no FFHV 0.097, RR 1.54, 95% CI 1.27 to 1.86). However, there was no difference between FFHV participants and non-participants in rates of children being vulnerable in at least one developmental domain at age 5 (PP: FFHV 0.551, no FFHV 0.557, RR 1.00, 95% CI 0.91 to 1.11). Conclusions: FFHV supports First Nations families in Manitoba by promoting childhood vaccination and connecting families to parenting resources in their communities, thus playing an important role in fulfilling the mandate of public health practice.